Analisis Perbandingan Produktifitas Tenaga Kerja Terhadap Analisa Harga Satuan Pekerjaan (AHSP) SNI 2024 dan Analisa di Lapangan - Yolanda Abdullah; Sartika Dewi Usman; Mohammad Yusuf Tuloli Usman (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Labor productivity is a crucial factor in determining the efficiency and success of construction project implementation. This study aims to measure labor productivity in the field using the Labor Utilization Rate (LUR) and compare it with the Unit Price Analysis (AHSP) SNI 2024 standards. The research was conducted on the HBEC Building construction project, focusing on the reinforcement work of the first-floor column in the meeting room area. The work sampling method with a productivity rating approach was employed to obtain actual labor productivity data on-site. The results show that the LUR value reached 82.97%, far above the minimum productivity threshold of 50%. This indicates that the labor productivity level on the project is considered high and satisfactory. Furthermore, a comparison between on-site productivity and the AHSP 2024 standards revealed that the average labor productivity on-site was 20 kg/day, while AHSP 2024 recorded 20.47 kg/day. The very small difference suggests that the actual labor productivity on-site is nearly equivalent to the national standards, reflecting efficient performance in project implementation. Overall, this study concludes that the work sampling method is effective in evaluating construction labor productivity. These findings are expected to serve as a practical reference for project managers and stakeholders in optimizing labor performance and improving project implementation efficiency in the future.